Experimental study on the natural circulation capability and heat transfer characteristic of liquid lead bismuth eutectic. (August 2019) - Shi, Leitai; Su, G.H.; Zhu, Fengjie; Bing, Tan; Hou, Yandong; Wei, Shiying; Wang, Chenglong; Tian, Wenxi; Qiu, Suizheng; Wu, Junmei
Abstract: The lead-bismuth eutectic(LBE)-cooled nuclear systems have significant natural circulation due to its large thermal expansion. Therefore, the passive safety of the reactor in postulated accidents is greatly improved. Moreover, the flow resistance and heat transfer characteristics are important to natural circulation ability of LBE-cooled system. In this paper, the natural circulation capability, the flow resistance and heat transfer characteristics were experimentally studied in the N atural C irculation C apability L oop(NCCL) facility. The research mainly includes four aspects: 1) start-up process of natural circulation; 2) capability of natural circulation; 3) flow resistance of LBE in an annular channel and 4) heat transfer in an annular channel. The results showed that a significant natural convection flow was generated in the experiment. Due to high thermal expansion of LBE, the natural circulation is quickly established and stabilized. The flow rate of natural circulation depends on the loop resistance and the temperature between heating section and cooling section. In our experiment, the maximum natural circulation flow rate was measured to be ∼0.81 kg/s. A new friction coefficient correlation was fitted and the results is slightly larger than the value calculated by the Blasius formula. For the convection heat transfer of liquid LBE in an annular channel, the heat conduction term is dominant, and the Nusselt number increases with the increase of Peclet number. Fitted experimental correlation of convection heat transfer of liquid LBE in annular channel is given. Highlights: The flow resistance and heat transfer experiments were conducted in a lead bismuth eutectic loop. The start-up process of natural circulation and capability of natural circulation were studied in this experiment. Fitted experimental correlations of friction coefficient and convection heat transfer of LBE in annular channel were given.